Sekolah Perjumpaan (Social School) as a Model of Molding Social Character and Humanity Values for Teenagers - Zulkipli Lessy; Abdul Munib; Saifullah Idris; Agus Mukmin (Universitas Pendidikan Mandalika, 2023)
This research aims to explore how Sekolah Perjumpaan (social school) in Midang Village, West Lombok, Nusa Tenggara Barat Province shapes the social character of local teenagers. The research method used was a case study with a qualitative approach. Data collection techniques used observations and in-depth interviews with mentors, religious leaders, governmental representatives, and members of the Midang Village community to discern social activities at Sekolah Perjumpaan. Data was then analyzed by categorizing similarities and differences in themes, previously managed through data reduction, data display, and data verification to yield findings. The findings showed that Sekolah Perjumpaan maintained social harmony, which was built upon the foundations of social norms as the ethical basis for strengthening intrapersonal relationships and a life guide adopted by teenagers. Social characters and human values were implemented at Sekolah Perjumpaan, which resulted in reciprocal shares and mutual respects that mirror the attitudes, such as proper self-positioning, good attitudes, and responsibility. Additionally, Sekolah Perjumpaan had existed to teach patience, sincerity, consciousness, or commitment to doing good.